Multidimensional immunotherapy for dry eye disease: current status and future directions - Huang, Duliurui; Li, Zhijie (Frontiers in Ophthalmology, 2024)
Dry Eye Disease (DED) is a multifactorial condition driven by tear film hyperosmolarity, immune dysregulation, and neuro-immune interactions. The immune system plays a central role in its pathogenesis, influencing both inflammation and ocular surface damage. While traditional immunotherapies like anti-inflammatory agents and immunosuppressants offer symptom relief, their long-term use is limited by side effects. This review focuses on emerging immunotherapies, including biologics, stem cell therapy, gene therapy, nanotechnology, and exosome-based treatments, all of which hold promise in modulating immune responses and promoting tissue repair. The relationship between the ocular microbiome and DED is also explored, with an emphasis on personalized immunotherapy. Key challenges for future research include identifying novel therapeutic targets, optimizing clinical translation, and evaluating the long-term efficacy of these innovative treatments.